"Саруул оюутны хүзүүний чимэг" толь бичгийн онцлог - Д., Бүрнээ (Mongolian Studies, 2023)
For centuries, Mongols have used reference books or dictionaries as a handbook when translating books and sutras on Buddhism. This article investigates the different features of the dictionary called "Intelligent Person’s Necklace" (Intelligent Person’s Necklace Elegant Pearl Rosary) written by Agvaandandar of Alashaa (1759-1840), a lexicographer of the 19th century, and identifies its differences by comparing pre and post dictionaries in terms of methodologies. This dictionary arranges headwords in the order of the Tibetan alphabet and as well as uses source texts to explain the words. The explanation is believed to play an important role in studying the relationship between lexicography and literature.